2018
DOI: 10.1186/s13075-018-1768-8
|View full text |Cite
|
Sign up to set email alerts
|

TNFα expressed on the surface of microparticles modulates endothelial cell fate in rheumatoid arthritis

Abstract: BackgroundRheumatoid arthritis (RA) is associated with a high prevalence of atherosclerosis. Recently increased levels of microparticles (MPs) have been reported in patients with RA. MPs could represent a link between autoimmunity and endothelial dysfunction by expressing tumor necrosis factor alpha (TNFα), a key cytokine involved in the pathogenesis of RA, altering endothelial apoptosis and autophagy. The aim of this study was to investigate TNFα expression on MPs and its relationship with endothelial cell fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…TNF-α is the main cytokine involved in the pathogenesis of RA, which can lead to atherosclerosis and endothelial dysfunction ( 67 , 68 ). It has been demonstrated that MPs in RA patients express TNF-α on their surface ( 69 ), Barbati et al, showed that MPs can induce the activation of asparaginase 3 and TNF-related apoptosis-inducing ligand (TRAIL) and TNF receptor, three independent signals that promote endothelial cell apoptosis, which can lead to the formation of atherosclerosis ( 62 , 70 ). All the above literatures indicate that extracellular vesicles in RA are not only involved in its pathogenesis, but also mainly related to inflammation, atherosclerosis, and impaired endothelial function.…”
Section: Evs and Autoimmune Diseasesmentioning
confidence: 99%
“…TNF-α is the main cytokine involved in the pathogenesis of RA, which can lead to atherosclerosis and endothelial dysfunction ( 67 , 68 ). It has been demonstrated that MPs in RA patients express TNF-α on their surface ( 69 ), Barbati et al, showed that MPs can induce the activation of asparaginase 3 and TNF-related apoptosis-inducing ligand (TRAIL) and TNF receptor, three independent signals that promote endothelial cell apoptosis, which can lead to the formation of atherosclerosis ( 62 , 70 ). All the above literatures indicate that extracellular vesicles in RA are not only involved in its pathogenesis, but also mainly related to inflammation, atherosclerosis, and impaired endothelial function.…”
Section: Evs and Autoimmune Diseasesmentioning
confidence: 99%
“…In addition, we showed that TNF-α carried on microparticles purified from RA patients was able to upregulate autophagy on endothelial cells. In vitro and ex vivo treatment with etanercept blocked this effect (Barbati et al, 2018).…”
Section: Tnf-αmentioning
confidence: 99%
“…Viñuela-Berni et al observed an increased number of MPs with CD3, CD14, CD19, CD41, and CD63E antigens in plasma of RA patients with high disease activity (DAS 28 > 5.1) [52]. The link between the intensity of inflammation in RA and the number and activity of released microparticles of endothelial origin was confirmed by Barbati et al The total pool of circulating MPs and endothelial MPs (EMPs) initially increased, then decreased after four months of anti-TNFα therapy [58]. The microparticles with CD3, CD14, CD19, CD41, and CD63E antigens also stimulated secretion of TNFα and IL-1, IL-17 by monocytes in vitro [52].…”
Section: Role Of Microparticles In Inflammatory Joint Diseasesmentioning
confidence: 99%